Impact of the COVID-19 Pandemic on Acute Upper Gastrointestinal Bleeding in Xingtai City. (8th March 2021) - Duan, Zhihui; Duan, Qiong; Liu, Kun; Zhang, Xiaochong; Zhou, Shengyun; on behalf of Xingtai Society of Digestive Endoscopy,
Abstract : Background and Aims . The coronavirus disease 2019 (COVID-19) has severely impacted the daily practice of gastrointestinal endoscopy worldwide. Most endoscopy centers in China were shut down in late January 2020. We investigated the impact of the shutdown on acute upper gastrointestinal bleeding (AUGIB) events in Xingtai City, Hebei Province, China. Methods . A web-based survey collected information on gastroscopy workload and AUGIB events. The study period was from 4 weeks before to 4 weeks after lockdown initiation in Xingtai City. Fourteen public gastrointestinal endoscopy centers performing emergency endoscopies were contacted via e-mail to collect weekly emergency gastroscopy volumes and the number of AUGIB events. AUGIB was defined as recent melena, hematemesis, or both, with an endoscopically visible source of bleeding. Results . Twelve (85.7%) of the 14 surveyed gastrointestinal endoscopy centers in the city- and county-level hospitals responded. Altogether, 4, 045 and 1, 077 gastroscopy procedures were performed 4 weeks before and after lockdown initiation (73.4% reduction), respectively. Peptic ulcer-related AUGIB and variceal AUGIB events showed a 58.5% and 52.9% decline, respectively, compared with pre-COVID-19 data. Although the absolute number of AUGIB events decreased during the pandemic (from 149 to 66), the likelihood of detecting AUGIB during gastroscopy increased (3.68% (pre-COVID-19 period) versus 6.13% (COVID-19 period); P < 0.05 ). Conclusion . The COVID-19 pandemic resulted in a considerable reduction in gastroscopy workload and AUGIB events; however, the likelihood of detecting AUGIB increased significantly during gastroscopies.